Pelaksanaan Sistem Informasi Kesehatan Ibu Hamil Di Puskesmas Mojogedang II Kabupaten Karanganyar - SAMSINI, Samsini; , Sri Sugiarsi, SKM, M.Kes (2016)
Mojogedang II sub-district health officer Karanganyar on the implementation of maternal health information system in the process of recording data pregnant women, pregnant women data processing and reporting of health data pregnant women frequent delays. The purpose of this study was to determine how the implementation of the Maternal Health Information System at Puskesmas Mojogedang II Karanganyar. This research is a qualitative descriptive study. Informants were selected researchers amounted to 7 people consisting of six village midwife and one person as triangulation. The data analysis of this study by using data reduction, data presentation, and conclusion. The results showed that the flow of data collection implementation of maternal health starts from Midwife Practice Mandiri, village midwives and health centers KIA officer. Input data with a computer. Processing of the data is still manual by writing in the register book and the book is still shaped data summary paper. Data Reporting PWS contains 13 indicators and report cases of obstetric emergencies. The problem is the human resources officer in the process of recording, processing and reporting.